2011
DOI: 10.1002/pon.2015
|View full text |Cite
|
Sign up to set email alerts
|

An individual‐based versus group‐based exercise and counselling intervention for improving quality of life in breast cancer survivors. A feasibility and efficacy study

Abstract: These preliminary results suggest a combined exercise and psychological counseling program is both a feasible and acceptable intervention for breast cancer survivors. Whilst both the individual and group interventions improved QOL above the clinically important difference, only the individual based intervention was significant when compared to UsC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
6
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 10 publications
1
31
6
2
Order By: Relevance
“…A study compared a group intervention to an individual approach to physical activity [43]. They found that while QoL improved in both groups of breast cancer survivors, only those in the individual intervention experienced a significant improvement compared to usual care [43]. The findings from our study are in contrast to that of others [43], in that ours was a group-based intervention and the majority of patients reported improvements in their QoL.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…A study compared a group intervention to an individual approach to physical activity [43]. They found that while QoL improved in both groups of breast cancer survivors, only those in the individual intervention experienced a significant improvement compared to usual care [43]. The findings from our study are in contrast to that of others [43], in that ours was a group-based intervention and the majority of patients reported improvements in their QoL.…”
Section: Discussioncontrasting
confidence: 75%
“…A study compared a group intervention to an individual approach to physical activity [43]. They found that while QoL improved in both groups of breast cancer survivors, only those in the individual intervention experienced a significant improvement compared to usual care [43].…”
Section: Discussionmentioning
confidence: 99%
“…Naumann et al (2011b) found that compliance rates were slightly higher (though this difference was not statistically significantly) in their independent physical activity compared with group-based physical activity group; the authors suggested that the inflexibility of group-based sessions may prove problematic for some cancer survivors who may wish to reschedule. Another benefit to individual activity is that programmes can be best tailored to meet the needs of the each survivor.…”
Section: Individual Versus Group Basedmentioning
confidence: 97%
“…In this method, the patient realizes his communication weak points in contact to others and learns the effective communication via received points from other patients at the same age and the therapist. In the group context, patients receive necessary education on anger management and train to get the meaning of others figures (14).…”
Section: Introductionmentioning
confidence: 99%